Diaphragm, battery cell, battery and electric device

By applying a coating made of nanomaterials on the separator of the cell, the risk of dendrites puncture of the membrane is solved, and the circulation performance and safety of the cell are improved.

CN119542669APending Publication Date: 2025-02-28CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311104010.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-30
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

During the charging and discharging process of metal cell, dendrites appear when metal ions deposit on the negative current collector, resulting in the puncture of the separator, increasing the risk of short-circuiting the battery cell and reducing the circulation performance.

Method used

A diaphragm is provided, including a base film and a coating located on at least one side of the base film, the coating is made of a nanomaterial to enhance the density and strength of the diaphragm and reduce the risk of being punctured.

Benefits of technology

By improving the strength and density of the separator, the risk of short circuit of the battery cell is reduced, and the circulation performance and volume energy density of the battery cell are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542669A_ABST
    Figure CN119542669A_ABST
Patent Text Reader

Abstract

The invention discloses a diaphragm, a battery monomer, a battery and an electric device, and belongs to the technical field of batteries. The diaphragm comprises a base membrane and a coating, the coating is located on the surface of at least one side of the base membrane, and the material of the coating comprises a nano material. The technical scheme provided by the embodiment of the invention is beneficial to improving the strength of the diaphragm and reducing the risk that the diaphragm is punctured, thereby being beneficial to reducing the risk of short circuit of the battery monomer and improving the cycle performance of the battery monomer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a diaphragm, a battery cell, a battery and an electrical device. Background Art

[0002] As environmental pollution becomes increasingly serious, the new energy industry has attracted more and more attention. In the new energy industry, battery technology is an important factor related to its development.

[0003] Metal battery cells have received extensive attention due to their high theoretical capacity and low redox potential. However, during the charge and discharge process of metal battery cells, metal ions are deposited on the negative electrode current collector to form dendrites, which have the risk of puncturing the diaphragm and causing the battery cell to short-circuit. Therefore, how to provide a diaphragm to improve the strength of the diaphragm, reduce the risk of puncture of the diaphragm, thereby reducing the short-circuit risk of the battery cell and improving the cycle performance of the battery cell is a technical problem that needs to be solved urgently. Summary of the invention

[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a diaphragm to improve the strength of the diaphragm, reduce the risk of the diaphragm being punctured, thereby reducing the risk of short circuit of the battery and improving the cycle performance of the battery cell.

[0005] In order to achieve the above-mentioned objectives, the present application provides a separator, a battery cell, a battery and an electrical device.

[0006] In a first aspect, a diaphragm is provided, comprising: a base film; and a coating, wherein the coating is located on a surface of at least one side of the base film, and the coating comprises a nano material.

[0007] The embodiment of the present application provides a diaphragm, including a base film and a coating located on at least one side of the base film. The material of the coating includes a nano material, so that the prepared coating is relatively dense, the strength of the diaphragm is relatively large, and the risk of the diaphragm being punctured can be reduced. Therefore, the diaphragm of the embodiment of the present application has a high strength and a low risk of being punctured, thereby reducing the risk of short circuits in battery cells, which is beneficial to improving the cycle performance of battery cells.

[0008] In a possible implementation, the thickness d1 of the base film and the thickness d2 of the coating satisfy: 0.3≤d1 / d2≤30.

[0009] When d1 / d2≥0.3, the coating and the base film have appropriate thicknesses, which is conducive to reducing the risk of increased resistance for metal ions to pass through the coating due to the relatively thick coating, thereby facilitating the reduction of the internal resistance of the battery cell and improving the cycling performance of the battery cell. When d1 / d2≤30, the coating and the base film have appropriate thicknesses, which is conducive to reducing the risk of the separator being punctured due to the relatively thin coating, thereby facilitating the reduction of the short-circuit risk of the battery cell and improving the cycling performance of the battery cell.

[0010] In a possible implementation, 1 < d1 / d2 ≤ 30; optionally, 3 ≤ d1 / d2 ≤ 12. In this way, it is beneficial to further balance the internal resistance of the battery cell and the strength of the separator, thereby facilitating the improvement of the cycling performance of the battery cell.

[0011] In a possible implementation, the coating includes organic nanomaterials. Organic nanomaterials have a relatively large molecular weight, and the coating prepared from organic nanomaterials has higher strength, thereby further improving the strength of the separator. In addition, the coating prepared from organic nanomaterials has a relatively high density, so that a coating with a relatively small thickness of organic nanomaterials can be prepared, which is beneficial to reducing the space occupied by the separator and improving the volumetric energy density of the battery cell.

[0012] In a possible implementation, the organic nanomaterials include at least one of aromatic ring polymers, heteroaromatic ring polymers, aramid fibers, or polyurethane fibers. The above-mentioned organic nanomaterials have a relatively large surface area, have good wettability to the electrolyte, and can store part of the electrolyte, so that during the charge and discharge cycles of the battery, they play a role in supplementing the electrolyte, which is beneficial to improving the cycling performance of the battery cell.

[0013] In a possible implementation, the organic nanomaterials include at least one of aramid fibers or polyurethane fibers; optionally, the aramid fibers include at least one of poly(p-phenylene terephthalamide) fibers, polyphenylene ether ketone fibers, or polyphenylene sulfide fibers; optionally, the polyurethane fibers include polyurethane.

[0014] The above-mentioned organic nanomaterials have a fibrous structure, so that the prepared coating has relatively high strength, and the risk of the separator being punctured is further reduced.

[0015] In a possible implementation, the coating includes inorganic nanomaterials.

[0016] The coating prepared from inorganic nanomaterials has relatively high stiffness and hardness, which is beneficial to reducing the risk of the separator being punctured.

[0017] In a possible implementation, the inorganic nanomaterial includes: at least one of silicon dioxide, aluminum oxide, zirconium trioxide or boehmite; optionally, the inorganic nanomaterial includes: at least one of silicon dioxide or aluminum oxide. The above inorganic nanomaterials are easy to obtain and are convenient for the preparation of the coating.

[0018] In a possible implementation, the thickness d1 of the base film satisfies: 5μm≤d1≤30μm. When the thickness d1 of the base film is not less than 5μm, the base film has a more suitable thickness, so that the diaphragm has a higher puncture resistance; when the thickness d1 of the base film does not exceed 30μm, it is beneficial to reduce the space occupied by the diaphragm and improve the volume energy density of the battery cell.

[0019] In a possible implementation, the thickness d2 of the coating satisfies 1 μm ≤ d2 ≤ 14 μm. When the thickness of the coating does not exceed 14 μm, it is beneficial to reduce the resistance of ions passing through the coating, thereby reducing the internal resistance of the battery cell; when the thickness of the coating is not less than 1 μm, it is beneficial to improve the puncture resistance of the diaphragm.

[0020] In a possible implementation, the coating includes a first coating and a second coating, and along the thickness direction of the separator, the base film is located between the first coating and the second coating. In this way, in the process of placing the separator on the positive electrode sheet and the negative electrode sheet, since the surfaces of both sides of the base film are provided with coatings, it is not necessary to distinguish the different surfaces on both sides of the separator, which is conducive to simplifying the complexity of battery cell assembly.

[0021] In a possible implementation, the thickness d21 of the first coating satisfies: 0.5 μm ≤ d21 ≤ 7 μm, and / or the thickness d22 of the second coating satisfies: 0.5 μm ≤ d22 ≤ 7 μm. In this way, the first coating and the second coating have appropriate thicknesses, which facilitates the preparation of the first coating and the second coating.

[0022] In a possible implementation, the thickness d21 of the first coating layer is the same as the thickness d22 of the second coating layer. In this way, the diaphragm has good symmetry.

[0023] In a possible implementation, the porosity σ of the diaphragm satisfies: 30%≤σ≤55%.

[0024] When the porosity of the diaphragm σ≥30%, the diaphragm has a suitable number of ion transmission channels, so that the barrier for metal ions to pass through the coating is low, which is conducive to reducing the internal resistance of the battery cell, slowing down the temperature rise of the battery cell, and improving the reliability of the battery cell; when σ≤55%, the porosity of the diaphragm is small, and the coating in the diaphragm is dense, so that the diaphragm has a higher strength, which is conducive to further reducing the risk of the diaphragm being punctured. In addition, when 30%≤σ≤55%, the metal ions have a more suitable transmission flux, and the metal ions can pass through the diaphragm more evenly and deposit evenly on the negative electrode current collector, which is conducive to slowing down or inhibiting the growth of dendrites, thereby further reducing the risk of dendrites puncturing the diaphragm.

[0025] In a possible implementation, the porosity σ of the separator satisfies: 45%≤σ≤55%. In this way, it is helpful to further take into account the internal resistance of the battery cell and the strength of the separator.

[0026] In a possible implementation, the Young's modulus E1 of the diaphragm in the length direction satisfies: E1 ≥ 8 MPa; optionally, E1 ≥ 9.5 MPa.

[0027] In a possible implementation, the Young's modulus E2 of the diaphragm in the width direction satisfies: E2 ≥ 5.3 MPa; optionally, E2 ≥ 7.3 MPa.

[0028] The Young's modulus of the diaphragm is large, so the diaphragm has a large strength. In this way, the strength of the diaphragm is greater than the force exerted on the diaphragm by the growth of dendrites, which can reduce the risk of dendrites piercing the diaphragm.

[0029] In a possible implementation, the base film includes at least one of a polyethylene film, a polypropylene film, or a composite film formed by a polyethylene film and a polypropylene film. In this way, it is convenient to select a suitable base film according to actual needs.

[0030] In a second aspect, a battery cell is provided, comprising the separator in the first aspect and any possible implementation thereof.

[0031] In a possible implementation, the battery cell is an alkali metal battery cell; optionally, the battery cell is a sodium metal battery cell. Alkali metal battery cells are prone to form dendrites on the negative electrode during the charge and discharge process. By providing the separator in the above embodiment in the alkali metal battery cell, the risk of internal short circuit of the battery cell is reduced and the cycle performance is improved.

[0032] In a possible implementation, the battery cell is a secondary battery cell.

[0033] In one possible implementation, the battery cell is suitable for fast charging scenarios. In fast charging scenarios, the battery cell has a larger charge and discharge current, the ion transmission rate becomes faster, and the growth rate of dendrites also becomes faster. The diaphragm of the battery cell of this embodiment has a higher strength, so that it can play a better protective role, and the risk of being punctured by dendrites is reduced, so that the battery cell can be used in fast charging scenarios.

[0034] In a third aspect, a battery is provided, comprising the battery cell in the second aspect and any possible implementation thereof.

[0035] In a fourth aspect, an electrical device is provided, comprising the battery described in the third aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 A schematic diagram of a diaphragm according to an embodiment of the present application;

[0037] Figure 2 A schematic diagram of a diaphragm according to an embodiment of the present application;

[0038] Figure 3 A schematic diagram of a diaphragm according to an embodiment of the present application;

[0039] Figure 4 A schematic diagram of a battery cell according to an embodiment of the present application;

[0040] Figure 5 A schematic diagram of a battery according to an embodiment of the present application;

[0041] Figure 6 FIG. 1 is a schematic diagram of an electrical device according to an embodiment of the present application. DETAILED DESCRIPTION

[0042] Below, the embodiments of the diaphragm, battery cell, battery, and electrical device of the present application are specifically disclosed in detail with appropriate reference to the drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0043] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0044] If there is no special description, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution. If there is no special description, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.

[0045] With the increasing severity of environmental pollution, the new energy industry has attracted more and more attention. In the new energy industry, battery technology is an important factor related to its development. Batteries include ion batteries and metal batteries. Ion batteries include lithium-ion batteries, sodium-ion batteries, etc., and metal batteries include lithium metal batteries, sodium metal batteries, etc. Metal batteries have received widespread attention due to their high theoretical capacity and low redox potential. However, during the charge and discharge process of metal batteries, metal ions are deposited on the negative electrode collector to form dendrites. As the dendrites grow, the dendrites easily pierce the diaphragm, causing the positive and negative electrodes of the battery to overlap, thereby causing an internal short circuit of the battery. After the internal short circuit of the battery occurs, the cycle performance is reduced. Therefore, how to provide a diaphragm with higher strength to reduce the risk of the diaphragm being pierced by dendrites, thereby reducing the short circuit risk of battery cells and improving the cycle performance of battery cells is a technical problem that needs to be solved urgently.

[0046] In view of this, the present application provides a diaphragm, which includes a base film and a coating located on at least one side of the base film. The coating includes nanomaterials, so the prepared coating is denser, the strength of the diaphragm is greater, and the risk of the diaphragm being punctured can be reduced, thereby reducing the risk of short circuit of the battery and improving the cycle performance of the battery.

[0047] [Diaphragm]

[0048] Figure 1 FIG. 1 is a schematic diagram of the structure of a diaphragm according to an embodiment of the present application. Figure 1 As shown, the diaphragm 1 includes a base film 10 and a coating layer 11 , wherein the coating layer 11 is located on at least one side of the base film 10 .

[0049] The base film 10 has two opposite surfaces along the thickness direction of the base film 10. The thickness direction of the base film 10 can be Figure 1 The z direction in .

[0050] For example, Figure 1 As shown, the coating 11 can be located on the surface of one side in the thickness direction of the base film 10. In other arrangements, the coating 11 can also be located on the surfaces of both sides in the thickness direction of the base film 10, that is, the two opposite surfaces in the thickness direction of the base film 10 are provided with the coating 11.

[0051] The coating 11 includes nanomaterials. Compared with non-nanomaterials, the coating 11 made of nanomaterials has the following advantages. (1) The particles of nanomaterials are smaller, and the gaps between particles are smaller, so it is not easy for dendrites to pass through the gaps, so the coating 11 made of nanomaterials has a more obvious barrier effect on dendrites; (2) The growth of dendrites along the thickness direction of the coating 11 is hindered, and the growth direction of the dendrites changes, for example, from a direction perpendicular to the coating 11 to a direction parallel to the coating 11; (3) The gaps between the particles of nanomaterials are smaller, and the number of gaps is larger. The gaps can guide ions to pass through, and then guide the ions to be uniformly deposited on the negative electrode current collector, further reducing the growth of dendrites; (4) The coating 11 made of nanomaterials is denser, has a larger Young's modulus and strength, and has a stronger ability to resist dendrite penetration.

[0052] The coating 11 includes nanomaterials, so that the coating 11 is denser, the diaphragm 1 has higher strength, and the risk of the coating 11 being punctured by dendrites is further reduced.

[0053] In addition, due to the provision of the coating 11, the coating 11 and the separator 1 have higher strength, thereby reducing the thickness requirement of the base film 10, which is beneficial to reducing the thickness of the base film 10 and the separator 1, thereby facilitating improving the energy density of the battery cell.

[0054] The embodiment of the present application provides a diaphragm 1, comprising a base film 10 and a coating 11 located on at least one side of the base film 10, wherein the coating 11 comprises a nano material and is relatively dense, so that the diaphragm 1 has a relatively high strength. Therefore, the diaphragm 1 of the embodiment of the present application has a relatively high strength, and the risk of the diaphragm 1 being punctured by dendrites is relatively low, thereby reducing the risk of short circuits in battery cells, which is beneficial to improving the cycle performance of battery cells.

[0055] In some embodiments, the thickness d1 of the base film 10 and the thickness d2 of the coating 11 satisfy: 0.3≤d1 / d2≤30. For example, d1 / d2 is 30, 25, 20, 15, 10, 5, 3, 1, 0.5, 0.3 or any value within the above range.

[0056] The thickness d1 of the base film 10 may be an average thickness of the base film 10 , for example, an average value of a maximum thickness and a minimum thickness.

[0057] The thickness d2 of the coating 11 may be an average thickness of the coating 11 , for example, an average of a maximum thickness and a minimum thickness.

[0058] The base film 10 may be a porous film, the porosity of the base film 10 is less than the porosity of the coating 11, and the coating 11 is denser than the base film 10. When the thickness of the diaphragm 1 is constant, the greater the thickness of the coating 11, the smaller the porosity of the diaphragm 1, the greater the strength of the diaphragm 1, and thus the lower the risk of the diaphragm 1 being punctured.

[0059] For example, d1 / d2 may be less than 1, that is, 0.3≤d1 / d2≤1. In this way, the thickness of the base film 10 is less than the thickness of the coating 11, and the separator 1 has a higher strength. And because the coating 11 is denser, a base film 10 with a smaller thickness can be provided, and the separator 1 has a smaller thickness, which is beneficial to improve the energy density of the battery cell.

[0060] When d1 / d2≥0.3, the coating 11 and the base film 10 have a relatively suitable thickness, which is beneficial to reducing the risk of increased resistance and potential barriers for metal ions (for example, sodium ions in sodium metal batteries, lithium ions in lithium metal batteries) to pass through the coating 11 due to the thick coating 11, thereby helping to reduce the internal resistance of the battery cell and improve the cycle performance of the battery cell.

[0061] When d1 / d2≤30, the ratio of the thickness of the coating 11 to the base film 10 is more appropriate. The coating 11 and the base film 10 have appropriate thicknesses, which is beneficial to reduce the risk of puncturing the diaphragm 1 due to the thin coating 11, so that the diaphragm 1 has higher strength and the risk of puncturing the diaphragm 1 by dendrites is reduced.

[0062] By setting 0.3 ≤ d1 / d2 ≤ 30, the battery cell has a suitable internal resistance, and the separator 1 has a suitable strength, so that the strength of the separator 1 and the internal resistance of the battery cell can be taken into account, and then the battery cell has high cycle performance.

[0063] In some embodiments, 1 < d1 / d2 ≤ 30. In this way, the thickness of the base film 10 is greater than the thickness of the coating 11, and the difficulty for metal ions to pass through the coating 11 is reduced, which is beneficial to further reducing the internal resistance of the battery cell.

[0064] In some embodiments, 3 ≤ d1 / d2 ≤ 12. In this way, the internal resistance of the battery cell and the strength of the separator 1 can be further taken into account, so that the battery cell has a high cycle life.

[0065] In some embodiments, the coating 11 includes organic nanomaterials.

[0066] The organic nanomaterials have a large molecular weight. The coating 11 prepared from the organic nanomaterials has higher strength, so that the strength of the separator 1 can be further improved. In addition, the coating 11 prepared from the organic nanomaterials has a high density, so that the coating 11 of the organic nanomaterials with a smaller thickness can be prepared, which is beneficial to reducing the space occupied by the separator 1 and improving the volume energy density of the battery cell.

[0067] In some embodiments, the organic nanomaterials include at least one of aromatic ring polymers, heteroaromatic ring polymers, aramid fibers or polyurethane fibers.

[0068] For example, the aromatic ring polymer may include at least one of polyethylene terephthalate or polybutylene terephthalate.

[0069] For example, the heteroaromatic ring polymer may include at least one of polyaniline, polyimide, polybiphenyltetracarboximide or biphenyltetracarboxylic dianhydride.

[0070] For example, the aramid fibers may include at least one of polyphenylene sulfide fibers, polyether ketone fibers or poly(p-phenylene terephthalamide) fibers.

[0071] For example, the polyurethane fibers may include polyurethane.

[0072] The above-mentioned organic nanomaterials have a large surface area and good wettability to the electrolyte. The coating 11 can store part of the electrolyte, so that in the charge and discharge cycles of the battery, it plays a role in supplementing the electrolyte, which is beneficial to improving the cycle performance of the battery cell.

[0073] In some embodiments, the organic nanomaterial comprises at least one of aramid fiber or polyurethane fiber. Optionally, the aramid fiber comprises at least one of polyterephthalamide fiber, polyphenylene ether ketone fiber or polyphenylene sulfide fiber. Optionally, the polyurethane fiber comprises polyurethane.

[0074] Aramid fibers and polyurethane fibers have a fibrous structure. The coating 11 prepared from the above nanofiber materials has high density and strength, and the diaphragm 1 has high strength, which is beneficial to further reduce the risk of the diaphragm 1 being punctured by dendrites.

[0075] In the embodiments of the present application, other organic nanomaterials may also be used, and the embodiments of the present application include but are not limited to these.

[0076] In some embodiments, the material of the coating 11 includes an inorganic nanomaterial. The coating 11 made of the inorganic nanomaterial has high rigidity and hardness, and also has a strong Young's modulus, which is beneficial to reduce the risk of the diaphragm 1 being punctured.

[0077] In some embodiments, the inorganic nanomaterial includes at least one of silicon dioxide SiO2, aluminum oxide Al2O3, zirconium oxide Zr2O3 or boehmite; alternatively, the inorganic nanomaterial includes at least one of silicon dioxide or aluminum oxide. The above inorganic nanomaterials are easy to obtain and facilitate the preparation of the coating 11.

[0078] In some embodiments, the coating 11 includes inorganic nanomaterials and organic nanomaterials.

[0079] In some embodiments, the thickness d1 of the base film 10 satisfies: 5 μm≤d1≤30 μm. For example, d1 is 5 μm, 8 μm, 10 μm, 14 μm, 20 μm, 28 μm, 30 μm or any value within the above range.

[0080] When the thickness d1 of the base film 10 is not less than 5 μm, the base film 10 has a more suitable thickness, so that the diaphragm 1 has a higher strength; when the thickness d1 of the base film 10 does not exceed 30 μm, it is beneficial to reduce the space occupied by the diaphragm 1 and improve the volume energy density of the battery cell.

[0081] In some embodiments, the thickness d2 of the coating 11 satisfies 1 μm ≤ d2 ≤ 14 μm. When the thickness of the coating 11 does not exceed 14 μm, it is beneficial to reduce the resistance of ions passing through the coating 11, thereby reducing the internal resistance of the battery cell; when the thickness of the coating 11 is not less than 1 μm, it is beneficial to improve the puncture resistance of the diaphragm 1.

[0082] Figure 2 Schematic diagram of the structure of a diaphragm according to an embodiment of the present application. Figure 2As shown, the coating layer 11 includes a first coating layer 111 and a second coating layer 112 , and along the thickness direction of the diaphragm 1 , the base film 10 is located between the first coating layer 111 and the second coating layer 112 .

[0083] The first coating layer 111 and the second coating layer 112 may have the same thickness or different thicknesses.

[0084] In the case where the coating 11 is provided on only one side of the surface of the base film 10, when the separator 1 is placed on the positive electrode sheet and the negative electrode sheet, the side of the separator 1 provided with the coating 11 is placed toward the negative electrode sheet, so that the dendrites on the negative electrode sheet are blocked. In this embodiment, since the coating 11 is provided on both sides of the surface of the base film 10, it is not necessary to distinguish the different surfaces on both sides of the separator 1, which is conducive to simplifying the complexity of battery cell assembly.

[0085] In some embodiments, the thickness d21 of the first coating layer 111 satisfies: 0.5 μm≤d21≤7 μm, and / or the thickness d22 of the second coating layer 112 satisfies: 0.5 μm≤d22≤7 μm.

[0086] d21 can be 0.5μm, 1μm, 3μm, 5μm, 6μm, 7μm or any value within the above range; d22 can be 0.5μm, 1μm, 3μm, 5μm, 6μm, 7μm or any value within the above range.

[0087] In this embodiment, the first coating layer 111 and the second coating layer 112 have suitable thicknesses, which facilitates the preparation of the first coating layer 111 and the second coating layer 112 .

[0088] In some embodiments, the thickness d21 of the first coating layer 111 is the same as the thickness d22 of the second coating layer 112. In this way, the diaphragm has good symmetry and the preparation process of the first coating layer 111 and the second coating layer 112 is simplified.

[0089] In some embodiments, the porosity σ of the separator 1 satisfies: 30%≤σ≤55%. For example, σ is 55%, 50%, 45%, 40%, 30% or any value within the above range.

[0090] The porosity of the diaphragm 1 can reflect the density of the coating 11 . The smaller the porosity of the diaphragm 1 , the denser the coating 11 , the higher the strength of the diaphragm 1 , and the lower the risk of the diaphragm 1 being punctured.

[0091] The porosity of the separator 1 is related to the material of the coating 11, the thickness of the coating 11 and the base film 10. For example, when the thickness of the separator 1 is constant, the greater the thickness of the coating 11, the smaller the porosity of the separator 1.

[0092] When the porosity σ of the diaphragm 1 is ≥30%, the diaphragm 1 has a suitable number of ion transmission channels, so that the barrier for metal ions to pass through the coating 11 is low, which is beneficial to reducing the internal resistance of the battery cell, slowing down the temperature rise of the battery cell, and improving the reliability of the battery cell; when σ≤55%, the porosity of the diaphragm 1 is small, and the coating 11 in the diaphragm 1 is denser, so that the diaphragm 1 has a higher strength, which is beneficial to further reduce the risk of the diaphragm 1 being punctured. In addition, when 30%≤σ≤55%, the metal ions have a more suitable transmission flux, and the metal ions can pass through the diaphragm 1 more evenly and deposit evenly on the negative electrode current collector, which is beneficial to slowing down or inhibiting the growth of dendrites, thereby further reducing the risk of dendrites puncturing the diaphragm 1.

[0093] In some embodiments, 45%≤σ≤55%. This is helpful to further consider the internal resistance of the battery cell and the strength of the separator.

[0094] Figure 3 Schematic diagram of the structure of a diaphragm according to an embodiment of the present application. Figure 3 It can be a top view of the diaphragm 1, Figure 3 The x direction is the length direction of the membrane 1, and the y direction is the width direction of the membrane 1. During the preparation and transportation of the membrane 1, the length direction of the membrane 1 is greater than the width direction of the membrane 1, wherein the length direction of the membrane 1 is the transportation direction of the membrane 1, and the width direction is parallel to the surface where the membrane 1 is located and perpendicular to the length direction.

[0095] It should be noted that after the preparation of the separator 1 is completed, the separator 1 can be cut to test the tensile strength. After cutting, the length of the separator 1 is not necessarily greater than the width.

[0096] In some embodiments, the Young's modulus E1 of the diaphragm 1 in the length direction satisfies: E1 ≥ 8 MPa; optionally, E1 ≥ 9.5 MPa.

[0097] E1 can be 8 MPa, 8.5 MPa, 9.5 MPa or any value within the above range; E2 can be 5.3 MPa, 6 MPa, 7.3 MPa, 8 MPa or any value within the above range.

[0098] In some embodiments, the Young's modulus E2 of the diaphragm 1 in the width direction satisfies: E2 ≥ 5.3 MPa. Optionally, E2 ≥ 7.3 MPa.

[0099] When testing the Young's modulus of the diaphragm 1, a tensile force is applied along the length direction of the diaphragm 1. The Young's modulus of the diaphragm 1 in the length direction is greater than that in the width direction.

[0100] During the growth of dendrites, a certain force will be exerted on the diaphragm 1. The Young's modulus of the diaphragm 1 is large, and the diaphragm 1 has a certain deformation ability and a large strength, so that it can withstand part of the force exerted on the diaphragm 1 by the growth of dendrites, thereby reducing the risk of the diaphragm 1 being punctured.

[0101] In some embodiments, the base film 10 includes at least one of a polyethylene film (PE film), a polypropylene film (PP film), or a composite film formed by a polyethylene film and a polypropylene film. In this way, it is convenient to select a suitable base film 10 according to actual needs.

[0102] The base film 1 may be a single-layer film or a composite film.

[0103] The composite film formed of polyethylene and polypropylene can be a multilayer film formed of PE film and PP film, such as PE film / PP film, PE film / PP film / PE film, etc. When the base film 1 is a multilayer film, the materials of each layer can be the same or different, without special restrictions.

[0104] The material of the base film 10 may also include at least one of glass fiber, non-woven fabric or polyvinylidene fluoride.

[0105] [Battery Cell]

[0106] An embodiment of the present application provides a battery cell, comprising the separator 1 in the above embodiment.

[0107] The embodiment of the present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. The battery cell may be an ion battery cell, a metal battery cell or the like.

[0108] Metal battery cells can also be called "negative electrode-free" battery cells. In the battery cell, the active metal ions are initially stored in the positive electrode active material. During the initial charging process, the metal ions move from the positive electrode to the negative electrode and deposit on the negative electrode current collector to form metal. Subsequently, during the discharge process, the metal ions detach from the negative electrode and embed into the positive electrode.

[0109] In a metal battery cell, the negative electrode may include only a negative electrode current collector, without including a negative electrode active material such as graphite.

[0110] In some embodiments, the battery cells are alkali metal battery cells; alternatively, the battery cells are sodium metal battery cells.

[0111] Since the problem of dendrites is more obvious in the process of charging and discharging of alkali metal battery cells, higher requirements are placed on the diaphragm 1. In alkali metal battery cells, the use of the high-strength diaphragm 1 of the embodiment of the present application can reduce the risk of dendrites piercing the diaphragm 1, thereby reducing the risk of internal short circuits in the battery cells and improving the cycle performance.

[0112] Alkali metal battery cells include lithium metal battery cells, sodium metal battery cells, potassium metal battery cells, and the like.

[0113] In some embodiments, the battery cell is suitable for fast charging scenarios. For example, the battery cell can be charged and discharged at a rate of 4C, that is, the battery cell is a 4C battery cell.

[0114] In the fast charging scenario, the battery cell has a larger charge and discharge current, the ion transmission rate becomes faster, and the growth rate of dendrites also becomes faster. The separator of the battery cell of this embodiment has a higher strength, so it can play a better protective role and reduce the risk of being punctured by dendrites, so that the battery cell can be used in the fast charging scenario.

[0115] Figure 4 Schematic diagram of a battery cell according to an embodiment of the present application. Figure 4 As shown, the battery cell 3 is a square battery cell and includes a housing 31 , an end cap assembly 32 and an electrode assembly 33 disposed in the housing 31 .

[0116] The electrode assembly 33 may be made of a positive electrode sheet, a negative electrode sheet and a separator through a winding process or a lamination process.

[0117] The end cap assembly 32 includes an electrode terminal 322, such as Figure 4 As shown, the end cap assembly 32 includes two electrode terminals 322, one of which is a positive electrode terminal and the other is a negative electrode terminal.

[0118] The battery cell 3 further includes a current collecting member 34 for connecting the tab 331 of the electrode assembly 33 and the electrode terminal 322 .

[0119] In some embodiments, the battery cell is a secondary battery cell, which can be used multiple times by charging and discharging.

[0120] In some embodiments, battery cells may be assembled into a battery module. The number of battery cells contained in the battery module may be one or more. The specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0121] [Positive electrode]

[0122] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer arranged on the positive electrode current collector.

[0123] The positive electrode current collector may be a metal foil or a composite current collector. For example, the positive electrode current collector may be an aluminum foil.

[0124] The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0125] The positive electrode film layer includes a positive electrode active material. The positive electrode active material can be a positive electrode active material for a battery known in the art. For example, in a lithium metal battery, the positive electrode active material is lithium iron phosphate, a ternary material, a lithium-rich manganese-based material, etc.; in a sodium metal battery, the positive electrode active material is a Prussian blue analog, a sodium-containing phosphate, a sodium-containing transition metal oxide, etc.

[0126] The positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0127] The positive electrode film layer may also optionally include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0128] [Negative electrode]

[0129] The negative electrode plate includes a negative electrode current collector. The negative electrode current collector may be a metal foil or a composite current collector. The negative electrode current collector may be a copper foil. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0130] [Electrolytes]

[0131] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present application embodiment has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0132] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent. The electrolyte salt may be a sodium salt, a lithium salt, etc. depending on the type of the battery monomer.

[0133] The lithium salt may include at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0134] Sodium salts may include NaPF6, NaBF4, NaN(SO2F)2, NaClO4, and the like.

[0135] The solvent may include at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0136] The electrolyte may also optionally include negative electrode film-forming additives, positive electrode film-forming additives, and may also include performance additives that can improve certain battery properties, such as improving battery overcharge performance, improving battery high temperature or low temperature performance, etc.

[0137] [Battery]

[0138] An embodiment of the present application provides a battery, comprising the battery cell in the above embodiment. Figure 5 Schematic diagram of a battery according to an embodiment of the present application. Figure 5 As shown, the battery 5 may include a plurality of battery cells (not shown in the figure).

[0139] The battery cells 3 can directly form the battery 5 , or can first form a battery module, and then multiple battery modules form the battery 5 .

[0140] [Electrical devices]

[0141] An embodiment of the present application provides an electrical device, comprising the battery described in the above embodiment.

[0142] Figure 6 FIG. 1 is a schematic diagram of an electrical device according to an embodiment of the present application. Figure 6 As shown, the present application provides an electrical device 6, including the battery in the above embodiment.

[0143] Optionally, the electrical device may also be an energy storage device, a lighting device, a spacecraft, etc. The embodiments of the present application include but are not limited to these.

[0144] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0145] [Example]

[0146] Example 1

[0147] In Example 1, the structure of the diaphragm 1 is shown in Figure 2 shown.

[0148] The thickness d1 of the base film 10 is 12 μm, the total thickness of the coating 11 is 1.5 μm, and the thickness of the first coating 111 and the second coating 112 are the same, both 0.75 μm. The base film 10 is a polypropylene film, and the material of the coating 11 is polyterephthalamide.

[0149] Example 2-17

[0150] The difference between Example 2-17 and Example 1 is that the thicknesses of the base film 10 and the coating layer 11 are different. Accordingly, the ratio d1 / d2 of the thickness d1 of the base film 10 and the thickness d2 of the coating layer 11 is also different.

[0151] Examples 18-19

[0152] The difference between Examples 18-19 and Example 1 is that the organic nanomaterials included in the coating 11 are different.

[0153] Examples 20-21

[0154] The difference between Examples 20-21 and Example 1 is that the coating 11 includes inorganic nanomaterials.

[0155] In Examples 20-21, the inorganic nanomaterials are different.

[0156] Embodiment 22

[0157] The difference between Example 22 and Example 1 is that a coating 11 is provided on one surface of the base film 10 .

[0158] Embodiment 23

[0159] The difference between Example 23 and Example 1 is that the thicknesses of the first coating layer 111 and the second coating layer 112 are different.

[0160] The separator 1 prepared in Examples 1-23 is applied to a sodium metal battery.

[0161] Embodiment 24

[0162] The difference between Example 24 and Example 1 is that the prepared diaphragm 1 is applied to a lithium metal battery.

[0163] Comparative Example 1

[0164] The difference between Comparative Example 1 and Example 1 is that the diaphragm only includes a base film but does not include a coating layer.

[0165] Comparative Example 2

[0166] The difference between Comparative Example 2 and Example 1 is that the material of the coating is not a nano material, but an aluminum oxide coating made of ordinary non-nano material.

[0167] The experimental parameters and test results of the embodiments and comparative examples can be found in Tables 1 and 2. In Table 2, the longitudinal Young's modulus is the Young's modulus in the direction of the tensile force applied to the separator, and the transverse direction is perpendicular to the longitudinal direction and parallel to the surface where the separator is located.

[0168] Table 1 Experimental parameters of embodiments and comparative examples

[0169]

[0170]

[0171] Table 2 Test results of embodiments and comparative examples

[0172]

[0173] [Preparation of sodium metal battery monomers]

[0174] (1) Preparation of positive electrode sheet: The positive electrode active material Na4Fe3(PO4)2(P2O7), the conductive agent carbon black Super P, and the binder polyvinylidene fluoride (PVDF) are ground and mixed evenly in a weight ratio of 90:5:5, and an appropriate amount of solvent N-methylpyrrolidone (NMP) is added and stirred evenly to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and then dried and cold pressed to obtain a positive electrode sheet.

[0175] (2) Preparation of negative electrode sheet: A carbon nanotube slurry with a solid content of 40% is coated on the negative electrode current collector. The negative electrode sheet is a copper foil with carbon nanotubes (CNT) coated on both sides with a total thickness of 4 μm on the negative electrode current collector.

[0176] (3) Isolation film: A polypropylene film is used as a base film, and a corresponding coating material is sprayed on the base film to prepare a coating.

[0177] (4) Preparation of electrolyte: solvent ethylene glycol dimethyl ether (DME) and electrolyte salt sodium hexafluorophosphate are mixed in corresponding proportions to obtain an electrolyte.

[0178] (5) Preparation of sodium metal battery cells: stack and wind the above-mentioned positive electrode plates, separators, and negative electrode plates in order to obtain an electrode assembly; place the electrode assembly in an outer package, add the above-prepared electrolyte, and obtain a sodium metal battery cell after packaging, standing, forming, aging and other processes.

[0179] Similarly, a lithium metal battery cell is prepared. In the lithium metal battery cell, the positive electrode active material is lithium iron phosphate and the electrolyte salt is lithium hexafluorophosphate.

[0180] [Cyclic performance test]

[0181] The cycle performance of the embodiments of the present application is reflected by the cycle life, and the test method of the cycle performance is introduced below.

[0182] At 25°C and normal pressure (0.1MPa), the battery cell is charged at a constant current of 0.5C to a voltage of 3.65V, and then discharged at a constant current of 1C to a voltage of 1.5V. This is a charge-discharge cycle. The capacity of the first discharge is 100%, and the charge-discharge cycle is repeated. When the SOH of the battery cell reaches 70%, the test is stopped and the cycle number is recorded. The cycle number is used as an indicator to evaluate the battery's room temperature cycle performance.

[0183] [Rate performance test]

[0184] The rate performance of the embodiment of the present application is reflected by the cycle life, and the test method of the rate performance is introduced below. Charging and discharging at a high rate current can reflect whether the battery cell is suitable for fast charging scenarios.

[0185] At 25°C and normal pressure (0.1MPa), the battery cell is charged at 4C constant current to a voltage of 3.65V, and then discharged at 4C constant current to a voltage of 1.5V. This is a charge and discharge cycle. The capacity of the first discharge is 100%, and the charge and discharge cycle is repeated. When the SOH of the battery cell reaches 80%, the test is stopped and the cycle number is recorded. The cycle number is used as an indicator to evaluate the battery's room temperature cycle performance.

[0186] [Internal resistance test]

[0187] In the embodiment of the present application, the internal resistance of the battery is reflected by the direct current resistance DCR. The test method of DCR is introduced below.

[0188] At 25°C, the battery was placed aside for 5 minutes, charged at a constant current rate of 1C to 3.65V, and then charged at a constant voltage until the current was less than or equal to 0.05C. At this time, the battery's state of charge (SOC) was 100%. After that, it was placed aside for 5 minutes, and then discharged at a constant current rate of 1C for 30 minutes to adjust the battery's state of charge (SOC) to 50%.

[0189] The battery cell with 50% SOC is placed for another 10 minutes, and then discharged at 4C constant current for 30 seconds. The voltage U1 at the last second of placement, the voltage U2 at the last second of 4C constant current discharge, and the current I of 4C constant current discharge are recorded. The DC impedance R of the battery cell at 25°C, 50% SOC, and 4C constant current discharge for 30 seconds is (U1-U2) / (I).

[0190] [Young's modulus test]

[0191] The elastic modulus of the isolation membrane has a well-known meaning in the art and can be measured by methods known in the art. For example, the test can be performed with reference to the national standard GB / T7757-2009. Specifically, the test can be performed by the following steps: the isolation membrane is cut into a test sample with a length of 50 mm and a width of 20 mm, and the elastic modulus is tested by a universal testing machine, with a stretching distance of 50 mm and a test speed of 20 mm / min.

[0192] [Porosity test]

[0193] The porosity of the diaphragm can be tested with reference to GB / T33052-2016. Cut the diaphragm into a suitable size and measure the volume V of the diaphragm; place the diaphragm in a bottle filled with hexadecane for a certain period of time so that the pores in the diaphragm are completely filled with hexadecane, and calculate the volume V2 of the absorbed hexadecane.

[0194] The porosity of the separator = (V2 / V1) x 100%.

[0195] [Test of diaphragm thickness]

[0196] The diaphragm was processed by ion polishing technology (also known as ion milling), and then the thickness of the base film and the thickness of the coating were tested by scanning electron microscopy (SEM).

[0197] [Testing of coating materials]

[0198] The materials in the coating can be determined by infrared spectroscopy and inductively coupled plasma technology (ICP). For example, the functional group information of the material in the coating can be determined by infrared spectroscopy, and then the type of material can be determined; the elements contained can be determined by ICP testing.

[0199] [Reduction in electrolyte volume]

[0200] The initial weight of the battery cell is recorded as M0, the weight of the battery cell after formation is recorded as M1, and the reduction in the amount of electrolyte is recorded as (M1-M0) / M0.

[0201] As shown in Examples 1-24 and Comparative Example 1, by providing a coating on the base film, the diaphragm has a larger Young's modulus and higher cycle performance. It should be noted that although the internal resistance DCR in Comparative Example 1 is lower than that in some embodiments, this is because the diaphragm in Comparative Example 1 is not provided with a coating.

[0202] As shown in Examples 1-24 and Comparative Example 2, the coating includes nanomaterials, and the prepared diaphragm has a larger modulus, so that the risk of the diaphragm being punctured by dendrites is further reduced. In addition, the coating includes nanomaterials, so that the coating has a smaller thickness while meeting the strength requirements, so that the battery cell has a higher energy density.

[0203] In summary, the diaphragm includes a base film and a coating, and the coating includes nanomaterials, which can enhance the strength of the diaphragm, reduce the risk of the diaphragm being punctured, reduce the risk of short circuits in battery cells, and improve the cycle performance of battery cells.

[0204] The diaphragm in the embodiment of the present application has high strength. When used in a battery cell, the risk of short circuit in the battery cell is reduced, so that the battery cell has a higher cycle performance. In addition, when the battery cell is charged and discharged with a large current rate, it is found that the battery cell still has a high cycle life at 80% SOH when charged and discharged at a current rate of 4C. Therefore, the diaphragm in the embodiment of the present application not only has higher strength and can be applied to metal battery cells; it also has better rate performance and can be used for 4C metal batteries and used in fast charging scenarios.

[0205] As shown in Example 1, when the thickness of the base film is 12 μm and the thickness of the coating is 1.5 μm, the separator has a larger Young's modulus, a better cycle life, and maintains a higher cycle life under a high rate charge and discharge current. As shown in Examples 1-24 and Comparative Example 2, the separators of Examples 1-24 have a smaller porosity, but the cycle life of Example 1 under high rate charge and discharge is higher than that of Comparative Example 2 under high rate.

[0206] In addition, when the coating thickness is small, the separator can have a certain puncture resistance, which is conducive to reducing the thickness of the separator and improving the volume energy density of the battery cell. Therefore, the battery cell of Example 1 can take into account better rate performance, higher cycle life and lower internal resistance.

[0207] As shown in Examples 1-16 and 17, when 0.3≤d1 / d2≤30, the battery cell has both a smaller internal resistance and a higher diaphragm strength, so that the cycle life of the battery cell is higher; when d1 / d2 is less than 0.3, the internal resistance of the battery cell is larger and the cycle performance is reduced.

[0208] As shown in combination with Example 1 and Examples 5 - 16, when 1 < d1 / d2 ≤ 30, the strength of the separator increases. However, at the same time, the internal resistance of the battery cell remains at a relatively low level, so the cycle life of the battery cell is still relatively high. As shown in combination with Example 1 and Examples 6 - 13, when 3 ≤ d1 / d2 ≤ 12, the separator has high strength, the battery cell has low internal resistance, and the battery cell has a relatively high cycle life and good rate performance.

[0209] As shown in combination with Examples 1 - 16, when the thickness of the base film satisfies 5μm ≤ d1 ≤ 30μm, the thickness of the coating d2 satisfies 1μm ≤ d2 ≤ 14μm, and d1 / d2 satisfies the above range, the battery cell has relatively high cycle performance. As shown in combination with Examples 1, 14 - 16, 19 - 20, the coating has a smaller thickness, and at the same time, the battery cell has a relatively high cycle life. Therefore, the battery cell can balance energy density and cycle life.

[0210] As shown in combination with Examples 1 - 16, the porosity of the separator is related to the material of the coating, and the thicknesses of the base film and the coating. By reasonably setting the thicknesses of the base film and the coating, the separator can have a suitable porosity, so that the battery cell has a suitable internal resistance; at the same time, the separator also has a relatively high Young's modulus and strength.

[0211] As shown in combination with Example 1 and Examples 18 - 19, Example 1 has a relatively large reduction in the amount of electrolyte, so the organic nanomaterials in Example 1 can better infiltrate the electrolyte. In addition, the organic nanomaterials in Example 1 and Example 19 have a fibrous structure, and the separator 1 has a relatively large Young's modulus.

[0212] As shown in combination with Example 1 and Examples 20 - 21, compared with inorganic nanomaterials, the separator prepared from organic nanomaterials has a relatively large Young's modulus, so that the separator can have a relatively high puncture resistance strength.

[0213] As shown in combination with Example 22 and Example 23, the separator of Example 1 of the present application can have coatings with various different structural settings.

[0214] As shown in combination with Example 24, the embodiments of the present application are applicable to lithium metal batteries. Compared with lithium metal batteries, in sodium metal batteries, generally speaking, the growth of dendrites is more obvious. The separator is applicable to sodium metal batteries and also applicable to lithium metal batteries. Similarly, it can also be applicable to other alkali metal batteries or ion batteries.

[0215] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A diaphragm, characterized in that: Comprising: Base film; A coating located on the surface of at least one side of the base film, the coating comprising nanomaterials.

2. The diaphragm according to claim 1, characterized in that The thickness d1 of the base film and the thickness d2 of the coating satisfy: 0.3 ≤ d1 / d2 ≤ 30; optionally, 1 < d1 / d2 ≤ 30; optionally, 3 ≤ d1 / d2 ≤ 12.

3. The diaphragm according to claim 1 or 2, characterized in that: The coating comprises organic nanomaterials.

4. The diaphragm according to claim 3, characterized in that The organic nanomaterials include at least one of aromatic ring polymers, heteroaromatic ring polymers, aramid fibers or polyurethane fibers.

5. The diaphragm according to claim 3 or 4, characterized in that: The organic nanomaterials include at least one of aramid fibers or polyurethane fibers; optionally, the aramid fibers include at least one of poly(p-phenylene terephthalamide) fibers, poly(phenylene ether ketone) fibers or polyphenylene sulfide fibers; optionally, the polyurethane fibers include polyurethane.

6. The diaphragm according to any one of claims 1 to 5, characterized in that The coating comprises inorganic nanomaterials.

7. The diaphragm according to claim 6, characterized in that The inorganic nanomaterials include at least one of silica, alumina, zirconium dioxide or boehmite; optionally, the inorganic nanomaterials include at least one of silica or alumina.

8. The diaphragm according to any one of claims 1 to 7, characterized in that The thickness d1 of the base film satisfies: 5 μm ≤ d1 ≤ 30 μm; optionally, 12 μm ≤ d1 ≤ 20 μm.

9. The diaphragm according to any one of claims 1 to 8, characterized in that The thickness d2 of the coating satisfies 1 μm ≤ d2 ≤ 14 μm; optionally, 1.5 μm ≤ d2 ≤ 2 μm.

10. The diaphragm according to any one of claims 1 to 9, characterized in that The coating comprises a first coating and a second coating, and along the thickness direction of the separator, the base film is located between the first coating and the second coating.

11. The diaphragm according to claim 10, characterized in that The thickness d21 of the first coating satisfies: 0.5 μm ≤ d21 ≤ 7 μm, and / or the thickness d22 of the second coating satisfies: 0.5 μm ≤ d22 ≤ 7 μm.

12. The diaphragm according to claim 10 or 11, characterized in that: The thickness d21 of the first coating is the same as the thickness d22 of the second coating.

13. The diaphragm according to any one of claims 1 to 12, characterized in that The porosity σ of the separator satisfies: 30% ≤ σ ≤ 55%; optionally, 45% ≤ σ ≤ 55%.

14. The diaphragm according to any one of claims 1 to 13, characterized in that The Young's modulus E1 in the length direction of the separator satisfies: E1 ≥ 8 MPa; optionally, E1 ≥ 9.5 Mpa.

15. The diaphragm according to any one of claims 1 to 14, characterized in that The Young's modulus E2 in the width direction of the separator satisfies: E2 ≥ 5.3 Mpa; optionally, E2 ≥ 7.3 Mpa.

16. The diaphragm according to any one of claims 1 to 15, characterized in that The base film comprises at least one of a polyethylene film, a polypropylene film or a composite film formed by a polyethylene film and a polypropylene film.

17. A battery cell, characterized in that: Comprising the separator according to any one of claims 1-16.

18. The battery cell according to claim 17, characterized in that: The battery cell is an alkali metal battery cell; optionally, the battery cell is a sodium metal battery cell.

19. A battery, characterized in that: Comprising the battery cell according to claim 17 or 18.

20. An electrical device, characterized in that: Comprising the battery according to claim 19.

Citation Information

Patent Citations

  • Battery diaphragm and application thereof

    CN104600230A

  • Battery isolating strengthening membrane and preparation method thereof

    CN108807786A

  • Modified composite diaphragm and preparation method thereof

    CN116315437A

  • NANO microporous diaphragm of post-crosslinked rubber and polyolefin composite, and manufacturing method thereof

    US20150325830A1